STRATEGI BAURAN PEMASARAN WINE SEBAGAI PRODUK PENUNJANG PARIWISATA (STUDI KASUS PT. SABABAY WINERY BALI) - Fransiska Tarigan, Agatha; Sudiarta, I Nyoman; Eka Mahadewi, Ni Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 6 No 1 (2018): Jurnal IPTA (July 2018), 2018)
Recently wine tourism products are being developed in Bali. Bali’s Wine is produced from the wineries, processed and produced in Bali which can be used as a tourist activity. This study aims to determine the strengths and weaknesses in wine products marketing and opportunities also, threats and know the strategy and marketing program of wine product that can be applied in PT. Sababay Winery. Data collection techniques used observation, interview, literature study, questionnaire, and documentation. Determination of the sample in this study is to use purposive sampling. Informant determination using key informant. This research use descriptive qualitative data analysi combine with likert scale analysis. The purpose of this study is to determine the characteristics of tourists, to find out the factors those influenced the decision of tourists to buy some souvenirs and also to find the most influenced factors. The methods of collecting data were through observation, interviewed, questionnaire, documentation, and literature study methods. The methods of analysis data were using descriptive quantitative method, through validity test, reliability and analysis of factors those supported by SPSS program 17.0 version. From this research, there are fourteen strength indicators and two indicators of weakness and indicators of opportunity as many as seven indicators and three indicators of threats owned by PT. Sababay Winery. Strategies and marketing programs that can be applied by PT. Sababay Winery is a product creation and development strategy, a strategy to increase wine product promotions, market expansion strategies, and marketing enhancement strategies.